Reasons, and emotional and physical health complications related to induced abortion of Kurdish women in Sanandaj, Iran - Ebtekar, Fariba (2012)
Abortion is illegal in Iran, yet women go through the risks for various reasons. A qualitative study was conducted with the purpose of exploring the reasons,emotional and physical health complications of Kurdish women who had an illegal, induced abortion one year before the interview. Twenty women were recruited through purposive sampling method from the maternity and family planning units in health-care centers in Sanandaj, Iran. The participants were interviewed in-depth for their abortion stories either at the health center or in their homes. A generic qualitative research approach was used to analyze the data. Trustworthiness was ensured through member checks, peer examination, and a documentation of an audit trail of the research activities. Three themes evolved from the women‟s response regarding the reasons why they decided to go in for the abortion; deciding to abort due to unintended pregnancy, deciding to abort due to self-pity, and deciding to abort due to family and social pressure. Nine themes related to women‟s emotional complications also emerged. Two themes sadness and ambivalence were identified prior to abortion. During the abortion, three themes loneliness, feeling of frustration and worry emerged and four themes that reflected women‟s emotions after abortion were fear, guilt, ambivalent emotions and regret. However, two themes, early-abortion complications and late-abortion complications, emerged from the data analysis regarding the women‟s physical health complications. A conceptual model also emerged from the findings. Through this qualitative study, an insight into Kurdish women‟s experiences of induced abortion was gained. Findings from this study can be used by Iran‟s Health Ministry to review and revise its policy to include pre-abortion and post abortion counseling. Midwives must take responsibility of effectively counseling couples before and after induced abortion, which may be performed for a variety of reasons. Post-abortion care for women with physical and emotional needs is also crucial. Recommendations for further researches are included.